P222 Pesticide exposure and chronic lymphocytic leukaemia using the spanish job-exposure matrix (matemesp). (1st September 2016) - Benavente, Yolanda; Suárez, Marta Rodríguez; Costas, Laura; Alguacil, Juan; Santibáñez, Miguel; Robles, Claudia; Alonso, Esther; Gonzalez-Barca, Eva; Dierssen-Sotos, Trinidad; Vázquez, Eva Gimeno; Aymerich, Marta; Campo, Elies; et al.
Abstract : Farming has been suggested to increase the risk of chronic lymphocytic leukaemia (CLL), and pesticides could contribute to this association. We evaluated associations between pesticides and CLL in the MCC-Spain study (318 CLL and 1665 controls) using a general job-exposure matrix developed for the Spanish population (MatEmESp). Ten pesticides were included in MatEmESp (Endosulfan, Chlorpyriphos, Methomil, Pyrethrin, Thiram, Captan, Dicuat, 2, 4 D, Atrazine and Diuron). The selection was done based on prevalence of recent use, toxicological evidence, existing regulations and threshold limit values in Spain. Forty four out of 482 CNO job titles (version 94, four digits) identified in MatEmESp as having exposure to pesticides were further grouped by occupational sectors (agriculture, wood-associated work, transport, cleaning-associated work and other occupations). Logistic regression models were adjusted for age, sex, region and education. Substantial correlation was observed between all pesticide agents (Spearman correlation coefficients ranged from 0.34 to 0.99). The estimated odds ratios for specific pesticides ranged from 1.24 to 1.52 although associations were not statistically significant (P > 0.05). Overall, having ever worked in any of the 44 occupations with exposure to pesticides was not associated with CLL (OR: 1.25; 95% CI: 0.92 to 1.70; P = 0.15). However, individuals who had worked in any of these occupations as their longest lifetime occupation were more likely to have CLL than controls (OR: 1.67, 95% CI: 1.05 to 2.65; P = 0.03). Occupations within the agricultural sector were found to be associated with CLL using both approaches: having ever worked and longest lifetime occupation. None of the other occupational sectors potentially exposed to the studied pesticides, those related to transport, cleaning or wood work, showed associations with the disease. These results provide further support to the association between farming and CLL. However, the correlation between the individual pesticides hampered the evaluation of their independent role.